ANALISIS PEMBERDAYAAN MASYARAKAT SELAKU PENGUSAHA UKM KAKI LIMA TERHADAP PENINGKATAN PENJUALAN DALAM KREDIT KUR PADA BRI JATIUWUNG KOTA TANGERANG - Nurhadi, Nurhadi (Universitas Bina Sarana Informatika, 2014)
Collect funds held in the bank forms a period varying deposits and withdrawals, such as checking accounts, checking accounts, time deposits, certificates of deposit, savings books and so on. or finance can be money or bills whose value is measured by money, for example a bank loan to finance the purchase of a house or a car. Then the existence of an agreement between the bank (credit) to the beneficiary customer credit (the debtor), that they agreed in accordance with the agreements that have been made. Methods This study took a sample test questionnaires on the sidewalk entrepreneurs in kecmatan jatiuwung Tangerang with a sample of 30 respondents. The magnitude of the numbers R Square (R2) of 0824 numbers can be used to see the effect on the society pemberdyaan Jatiuwung KUR credit services (coefficient determinant). This figure has the intention that the analysis of community empowerment as a sidewalk SMEs to credit services KUR BRI Jatiuwung was 82.4% and the remaining affected other variables. Calculated F = 63.309, compared to the F table using error level of 5% was obtained value of F table = 2.042 so F count> F table (63.309> 2042), then Ho is rejected and Ha is accepted, it means there is influence between SMEs empowerment as a sidewalk the KUR credit services on BRI Jatiuwung Keywords: banks, creditors, customers, entrepreneurship, marketing